Dissociation of blood-brain barrier disruption and disease manifestation in an aquaporin-4-deficient mouse model of amyotrophic lateral sclerosis. (August 2018) - Watanabe-Matsumoto, Saori; Moriwaki, Yasuhiro; Okuda, Takashi; Ohara, Shinji; Yamanaka, Koji; Abe, Yoichiro; Yasui, Masato; Misawa, Hidemi
Highlights: AQP4 overexpression is detected in ALS model mice and patients with ALS. No aberrant AQP4 localization is observed in other chronic or acute gliosis models. AQP4 deficiency improves BBB disruption in ALS mice. AQP4 deficiency accelerates disease onset and shortens lifespan in ALS model mice. Abstract: Aquaporin-4 (AQP4) is abundantly expressed in the central nervous system and is involved in the water balance in the cellular environment. Previous studies have reported that AQP4 expression is upregulated in rat models of amyotrophic lateral sclerosis (ALS), a fatal disease that affects motor neurons in the brain and spinal cord. In this study, we report that astrocytic AQP4 overexpression is evident during the course of disease in the spinal cord of an ALS mouse model, as well as in tissue from patients with ALS. AQP4 overexpression appears to be specifically associated with ALS because it was not induced by other experimental manipulations that produced acute or chronic gliosis. In order to examine the contribution of AQP4 to ALS disease development, we crossed AQP4 knockout mice with a mouse model of ALS. Significant improvement in blood-brain barrier (BBB) permeability was observed in the AQP4-deficient ALS mouse model. However, the time to disease onset and total lifespan were reduced in the AQP4-deficient ALS mouse model. The contradictory results suggest that changes in AQP4 may be context-dependent and further studies are required to understand the precise contribution of brain water balance in ALS.